Salivary hydroxyproline levels and gingivitis in 6-7 years children: a case-control study - Marzieh Mohammadi Moghadam; Hadi Nasiroddini; Freshteh Osmani (Open Exploration Publishing Inc., 2024)
Aim: Gingivitis is the most prevalent periodontal infection in children and adolescents. Various salivary markers have become potentially important in the early diagnosis of oral diseases, and some salivary amino acids play a significant role in predicting periodontal status. Therefore, this study investigated the relationship between the concentration of hydroxyproline in unstimulated saliva and the occurrence of gingivitis in 6-7 years children. Methods: This case-control study was conducted on children aged 6-7 years in elementary schools in Birjand from November 2022 to June 2023. A boy's school was randomly selected based on the list of primary schools in Birjand city. Then, among the students in the first grade of elementary school and after the initial examinations, they were assigned to study groups according to the presence of inflammation in the gums and consent to participate in the study. Data analysis was done using SPSS-19 and statistical tests such as chi-square and Mann-Whitney U tests were employed for data analysis at a significance level of 5%. Results: The unhealthy group had poorer dental health compared to the healthy group (P = 0.013) and there were no differences in the dental care attendance status of participants between the two groups (P = 0.288). The mean of salivary hydroxyproline levels in the unhealthy group was 0.197 ± 0.289 mg/L and in the healthy group was 0.079 ± 0.006 mg/L. This difference was statistically significant between 2 study groups (P = 0.001). Conclusions: It can be concluded that the level of hydroxyproline in unstimulated saliva samples can be used as a biomarker in the diagnosis of gingivitis. However, to confirm the results of this study, further studies with a larger sample size comparing different severities of periodontitis such as mild, moderate, and severe forms are needed.